2022
DOI: 10.3390/antibiotics11070864
|View full text |Cite
|
Sign up to set email alerts
|

Development of Wash-Durable Antimicrobial Cotton Fabrics by In Situ Green Synthesis of Silver Nanoparticles and Investigation of Their Antimicrobial Efficacy against Drug-Resistant Bacteria

Abstract: An environment friendly and wash-durable silver nanoparticle treatment of cotton fabrics was carried out by in situ reduction of silver nitrate using Azadirachta indica leaf extract. The wash durability of the silver nanoparticles treatment on the cotton fabric was improved by pretreating the fabrics by mercerization and by adopting hydrothermal conditions of 120 °C temperature and 15 psi pressure for the in situ synthesis. The silver nanoparticle treated fabrics were characterized using scanning electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…Consistent with the existing literature [54][55][56][57][58], our research findings highlight the outstanding antimicrobial activity of silver nitrate, zinc chloride, and tea tree oil, showing remarkable efficacy against all three bacterial strains. The observed percentages of antimicrobial activity are comparable to or higher than those reported in the literature for antimicrobial textiles targeting Gram-negative E. coli and K. pneumonia, as well as Gram-positive MRSA [51,[59][60][61][62][63][64][65]. However, it is important to note that our results revealed a discrepancy in effectiveness, with HM4005 and HM4072 exhibiting high efficacy (>80% bacterial reduction) against the tested Gram-negative bacteria species but demonstrating minimal activity against Gram-positive MRSA (0% and 25% bacterial reduction for HM4005 and HM4072, respectively).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Consistent with the existing literature [54][55][56][57][58], our research findings highlight the outstanding antimicrobial activity of silver nitrate, zinc chloride, and tea tree oil, showing remarkable efficacy against all three bacterial strains. The observed percentages of antimicrobial activity are comparable to or higher than those reported in the literature for antimicrobial textiles targeting Gram-negative E. coli and K. pneumonia, as well as Gram-positive MRSA [51,[59][60][61][62][63][64][65]. However, it is important to note that our results revealed a discrepancy in effectiveness, with HM4005 and HM4072 exhibiting high efficacy (>80% bacterial reduction) against the tested Gram-negative bacteria species but demonstrating minimal activity against Gram-positive MRSA (0% and 25% bacterial reduction for HM4005 and HM4072, respectively).…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with the existing literature [54][55][56][57][58], our research findings highlight the outstanding antimicrobial activity of silver nitrate, zinc chloride, and tea tree oil, showing remarkable efficacy against all three bacterial strains. The observed percentages of antimicrobial activity are comparable to or higher than those reported in the literature for antimicrobial textiles targeting Gram-negative E. coli and K. pneumonia, as well as Gram-positive MRSA [51,[59][60][61][62][63][64][65]. However, it is important to note…”
Section: Discussionsupporting
confidence: 75%
“…In this regard, Au nanoparticle can act alternatively as an acceptor and as a donor of electrons, which help the electron transmit in reduction and oxidation reactions (Khan et al, 2016). Besides, biocidal nature of the metallic nanoparticles, such as Au or Ag is effective in enhancing photocatalytic activity due to toxic effect of metal released to the solution (Changcun & Meng, 2020, Jain, Kongkham, et al, 2022). The large surfaces of Au nanoparticles along with their inherent ability to penetrate the bacterial cells, can significantly affect the deactivation of bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial properties of the silver nanoparticles were also effective at killing bacteria in the surrounding area [38]. In a study [223], cotton fibres coated with silver nanoparticles have shown a good release of antibiotics over a sustained period, with the release rate varying depending on the thickness of the coating. Overall, smart textiles with green nanomaterials have the potential to revolutionize drug delivery by providing a targeted, localized approach to treatment.…”
Section: Environmental and Medical Applications Of Smart Textiles Wit...mentioning
confidence: 99%